AEA Randomized Controlled Trials 2019
DOI: 10.1257/rct.4388-1.0
|View full text |Cite
|
Sign up to set email alerts
|

Using Household Grants to Benchmark the Cost Effectiveness of a USAID Workforce Readiness Program

Craig McIntosh

Abstract: We use a randomized experiment to compare a workforce training program to cash transfers in Rwanda. Conducted in a sample of poor and underemployed youth, this study measures the impact of the training program not only relative to a control group but relative to the counterfactual of simply disbursing the cost of the program directly to beneficiaries. While the training program was successful in improving a number of core outcomes (productive hours, assets, savings, and subjective well-being), cost-equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…As was the case in the one-year evaluation results from this study (McIntosh and Zeitlin, 2022), we find no evidence of complementarity; the combined arm demonstrates the impacts seen in either arm with no additional benefits arising from them being implemented together. Most of these outcomes represent a 'fade' of about 50% relative to the impacts seen in the midline study, meaning that roughly half of the benefit observed after one year is still present more than three years later.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…As was the case in the one-year evaluation results from this study (McIntosh and Zeitlin, 2022), we find no evidence of complementarity; the combined arm demonstrates the impacts seen in either arm with no additional benefits arising from them being implemented together. Most of these outcomes represent a 'fade' of about 50% relative to the impacts seen in the midline study, meaning that roughly half of the benefit observed after one year is still present more than three years later.…”
Section: Introductionsupporting
confidence: 56%
“…We find evidence that both interventions have sizeable impacts on primary economic outcomes relative to control, with cash transfers out-performing training, and that these impacts persist in the medium term, though they muted relative to the short term and no longer statistically distinguishable from one another. McIntosh and Zeitlin (2022) reported short-term impacts, finding that HD increased hours worked, monthly income, and productive assets, and that the impacts of cash transfers were significantly larger at cost-equivalent levels on the latter two domains; moreover, only cash transfers significantly moved consumption outcomes. The medium-term evidence presented here shows that HD continues to elevate productive hours per week by 3.3, productive assets are almost twice the control group, and an index of business knowledge is higher by 0.25 standard deviations even three year later.…”
Section: Introductionmentioning
confidence: 99%
“…While blinding of participants is impossible for CTs, blinding personnel and outcome assessment was mentioned in only one RCT. In it, blinding was not performed (McIntosh & Zeitlin, 2020). Overall, few studies (8/38) referred to preregistered protocols.…”
Section: Description Of Studies and Qualitymentioning
confidence: 99%
“…Although there is some preliminary evidence that CTs are cost-effective interventions compared to a USAID workforce readiness program (McIntosh & Zeitlin, 2020) and psychotherapy (Haushofer, Shapiro & Mudida, 2020), the work done to compare the cost-effectiveness of interventions in terms of SWB and MH is nascent, especially in LMICs. Our meta-analysis contributes to this literature by providing a comprehensive empirical foundation to compare the cost-effectiveness of cash transfers to interventions aimed at improving MH or SWB.…”
Section: Implications and Suggestions For Future Researchmentioning
confidence: 99%
“…In addition to the evidence synthesis, this review contributes to the growing literature of situating cash transfers as the “control” or standard of care. This is particularly relevant to studies assessing the cost-effectiveness of new interventions and their value compared to if a low-cost cash transfer programme were implemented as opposed to nothing [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%